Factors influencing treatment outcomes assessed by the American Board of Orthodontics Objective Grading System (ABO-OGS) - Tanyapak Kongboonvijit; Sirichom Satrawaha; Anupap Somboonsavatdee (BMC, 2023)
Abstract Background Treatment outcomes can be influenced by various factors. This study aimed to determine the association between predisposing patient- and treatment-related factors (demographic, cephalometric parameters, skeletal relationships, Discrepancy Index (DI), extractions, treatment type and duration) and treatment outcomes measures according to the American Board of Orthodontics Objective Grading System index (ABO-OGS). Methods Completed cases (N = 100) were included in this cross-sectional study. One calibrated examiner assessed DI, pretreatment lateral cephalometric parameters and ABO-OGS. Patient data, including sex, age, types of malocclusion, extractions, treatment type, and duration, were also collected. Intraexaminer reliability for each measurement was evaluated using the intraclass correlation coefficients. Multiple linear regression analysis, using the backward elimination method with a significance level (α) of 0.05, was used to determine which factors significantly influenced the ABO-OGS score. Results From the study, the overall mean ABO-OGS score was 11.36 points. Factors influencing the ABO-OGS score were pretreatment Wits values (p value = .000), L1-NB (°) (p value = .023) and treatment duration (p value = .019). Subjects with lower negative values of Wits and L1-NB (°) tended to have higher ABO-OGS scores. Additionally, the ABO-OGS score tended to be higher for subjects with longer treatment times. Conclusions The majority of treated subjects had satisfactory orthodontic treatment outcomes assessed by the ABO-OGS. The pretreatment severity of skeletal discrepancies determined by the Wits parameter, the degree of retroclined lower incisors and longer treatment duration negatively impacted the treatment outcomes.